The Influence of Organizational Commitment and Compensation on Employee Performance in the Production Division of PT Adis Dimension Footwear in Tangerang Regency - Marbun, Agnes; Soebadio, Bizzma Buana Amriki (AGUSPATI Research Institute, 2025)
The purpose of this study is to determine how much influence organizational commitment and compensation simultaneously have on employee performance in the Production section at PT. Adis Dimension Footwear, Tangerang Regency. This study uses a quantitative descriptive method, namely research that describes variables as they are supported by data in the form of numbers generated from actual conditions. The population in this study were all employees in the Production section at PT. Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 92 respondents. This study uses the slovin formula, so the sample in this study uses the entire population to be used as respondents as many as 1185 employees. The data collection techniques used were observation, questionnaires and documentation. The data analysis technique used multiple linear regression analysis using SPSS 26. The validity of the data was obtained through the t test (partial) and simultaneous F test. The results of this study indicate that (1) partially, organizational commitment significantly influences employee performance in the Production section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the t count value> t table (5.436> 1.987) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, compensation significantly influences employee performance in the Production section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the t count value> t table (5.351> 1.987) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, organizational commitment and compensation significantly influence employee performance in the Production section at PT. Adis Dimension Footwear Tangerang Regency, which is indicated by Fcount> Ftable (64.770> 3.10) with a significance level of 0.000, thus Ha is accepted and H0 is rejected. Based on the results of the study, it can be concluded that the variables of organizational commitment and compensation, both partially and simultaneously, have a significant influence on employee performance in the Production section at PT. Adis Dimension Footwear Tangerang Regency